Smartboards And School Culture Transformation: A Case Study Of The Use Of Digital Media In Pancasila Education Learning - Muntazarah, Fediyatun (Jurusan Teknik Informatika dan Komputer, 2025)
This study explores how the use of smartboards as digital media in Pancasila Education learning can trigger a transformation of school culture in public and private high schools in Makassar City. Using a descriptive qualitative case study approach, the study was conducted in one of the schools that has received smartboard assistance from the government, namely SMPIT Anugrah Hidayah and integrated it into Pancasila Education learning. Data were collected through observation, interviews with teachers and students, and school documentation. The results show that the use of smartboards not only increases student interaction and participation, but also creates a more active, collaborative, and nationally valued learning culture. Supporting factors include infrastructure readiness and teacher competency, while the main obstacles are the still dominant old culture and the lack of ongoing training. Recommendations for this study include strategies for strengthening teacher competency, updating school policies, and monitoring the integration of learning technology